Catalyst for producing alkylstyrene, process for the preparation thereof and use thereof

CN117920240BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211306050.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-24
Publication Date
2026-10-30
Estimated Expiration
2042-10-24

AI Technical Summary

Technical Problem

[0006]针对现有技术中存在的烷基苯乙烯的选择性不高的问题,本发明提供一种新的用于生产烷基苯乙烯的催化剂,该催化剂具有热裂解副产物少,烷基苯乙烯选择性高的特点

Benefits of technology

[0034]本发明提供的用于生产烷基苯乙烯的催化剂,各组分相互配合,具有更好的协同作用,有利于提高产物烷基苯乙烯的选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003906072130000041
    Figure BDA0003906072130000041
  • Figure BDA0003906072130000042
    Figure BDA0003906072130000042
  • Figure BDA0003906072130000101
    Figure BDA0003906072130000101
Patent Text Reader

Abstract

The application discloses a catalyst for producing alkylstyrene and a preparation method and application thereof. The catalyst comprises the following components in percentage by weight: (a) 65-70% of Fe2O3; (b) 16-20% of alkali metal oxide; (c) 9.0-13.5% of CeO2; (d) 0.5-3.5% of MoO3; and (e) 1.1-4.5% of alkaline earth metal oxide; wherein the weight ratio of the alkali metal to the alkaline earth metal is 4-10 in terms of oxide. The catalyst can effectively improve the selectivity of the target product in the reaction of alkyl ethylbenzene dehydrogenation for producing alkylstyrene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, specifically relating to a catalyst for the production of alkylstyrene, its preparation method, and its application. Background Technology

[0002] Styrene is an important organic raw material monomer with a wide range of applications. Due to the presence of the benzene ring, styrene is easily modified, resulting in a series of styrene derivatives. Alkyl styrene monomers, depending on their alkyl substituents, possess unique and excellent properties, meeting the specific performance requirements of various fields.

[0003] Methylstyrene can replace styrene monomers and is mainly used in the production of high-grade unsaturated polyester resins, modified alkyd resins, and vinyl resins. Resins produced using methylstyrene are widely used in impregnated insulating varnishes, coatings, and composite materials industries. In unsaturated polyester resins, partially or completely replacing styrene monomers with p-methylstyrene results in a lower vapor pressure, higher flash point, lower shrinkage in molded products, better thermal properties, and improved mechanical properties in glass fiber reinforced products. Monomers and copolymers produced using p-methylstyrene have a lower specific gravity, better flowability, and better thermal stability compared to styrene. In flame-retardant applications, p-methylstyrene polymers require less flame retardant to achieve the same flame-retardant effect, and the molecular structure of the polymer can be modified through chemical crosslinking and radiation.

[0004] p-tert-Butylstyrene (TBS) can be used in high-elasticity coatings, adhesives, and specialty copolymers. Compared to styrene, TBS has a lower vapor pressure and a higher flash point. TBS also exhibits higher oil affinity, higher solvent acceptability, and better hydrophobicity. p-tert-Butylstyrene polymers have a higher glass transition temperature, making them a suitable alternative to styrene in epoxy curing agents, fiber-reinforced polyesters, paints, specialty coatings, adhesives, and copolymers.

[0005] Alkyl styrene is mainly obtained through the dehydrogenation of alkyl ethylbenzene. Since the reaction is endothermic and involves an increase in the number of molecules, high temperature and low pressure favor the forward reaction. However, compared to ethylbenzene, alkyl ethylbenzene contains branched chains on its benzene ring, leading to increased side reactions such as thermal decomposition at higher reaction temperatures. For example, in US Patent 3631213A, the dehydrogenation of tert-butyl ethylbenzene produces numerous byproducts, resulting in a yield of less than 45% of the desired tert-butyl styrene. Summary of the Invention

[0006] To address the problem of low selectivity for alkylstyrene in existing technologies, this invention provides a novel catalyst for the production of alkylstyrene, which features low thermal cracking byproducts and high selectivity for alkylstyrene.

[0007] A first aspect of the present invention provides a catalyst for the production of alkylstyrene, comprising the following components by weight percentage of the total catalyst:

[0008] (a) 65%–70% Fe2O3;

[0009] (b) 16%–20% alkali metal oxides;

[0010] (c) 9.0%–13.5% CeO2;

[0011] (d) 0.5%–3.5% MoO3;

[0012] (e) 1.1% to 4.5% alkaline earth metal oxides;

[0013] The weight ratio of alkali metals to alkaline earth metals, calculated as oxides, is 4 to 10.

[0014] Furthermore, the alkali metal is K and Na, and the alkaline earth metal is Ba and Ca.

[0015] Furthermore, in the alkali metal, Na2O accounts for 1.5% to 10.0% of the total weight of the alkali metal oxide, and in the alkaline earth metal, CaO accounts for 50% to 95% of the total weight of the alkaline earth metal oxide.

[0016] Furthermore, the catalyst also includes at least two elements selected from the transition metals Sc, Y, Ti, and Zr, with a weight content of 0.05% to 0.50% based on oxides, preferably 0.1% to 0.3%.

[0017] Furthermore, the transition metal preferably includes at least one or two elements selected from Y and Ti, and more preferably includes both Y and Ti, wherein the weight ratio of Y to Ti, calculated as oxides, is 5 to 25.

[0018] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst for the production of alkylstyrene, comprising the following steps:

[0019] (1) Dissolve and mix the required amounts of alkali metal source and alkaline earth metal source in water to obtain mixture I;

[0020] (2) Mix the required amounts of iron source, cerium source, molybdenum source and pore-forming agent, then add the mixture I, wet mix, shape, dry and calcine to obtain the catalyst.

[0021] Further, in step (2), it is preferable to mix the transition metal precursor with the required amount of iron source, cerium source, molybdenum source and pore-forming agent, and then add the mixture I, wet mix, form, dry and calcine to obtain the catalyst.

[0022] Furthermore, in step (1), the alkali metal source and alkaline earth metal source are selected from one or more of carbonates and hydroxides.

[0023] Further, in step (2), the iron source is selected from iron oxide red and iron oxide yellow, the cerium source is selected from at least two of nitrates, carbonates and oxalates, the molybdenum source is selected from their soluble salts or oxides, and the transition metal precursor is selected from their soluble salts or oxides.

[0024] Further, in step (2), the pore-forming agent is selected from one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, guar gum, methyl cellulose, and hydroxyethyl cellulose, and its addition amount is 3% to 5% of the total weight of the catalyst raw materials.

[0025] Furthermore, in step (1), there is no particular limitation on the amount of water added. However, the moisture content should be reasonably controlled in conjunction with the molding requirements of step (2). For example, but not limited to, the amount of water added should account for 12% to 20% of the total weight of the catalyst raw materials.

[0026] Furthermore, in step (2), a cooling medium can be added outside the system as needed to reduce the temperature.

[0027] Furthermore, in step (2), the material discharge temperature during the wet mixing process is controlled at 40-75℃.

[0028] Further, in step (2), the drying conditions are: drying temperature of 50-100℃ and drying time of 4-24h.

[0029] Further, in step (2), the roasting is divided into three stages: the first stage is roasted at 250-380℃ for 4-8 hours, the second stage is roasted at 600-720℃ for 4-8 hours, and the third stage is roasted at 780-870℃ for 3-6 hours.

[0030] A third aspect of the present invention provides the application of the above-mentioned catalyst in the dehydrogenation reaction of alkyl ethylbenzene to produce alkyl styrene.

[0031] Furthermore, the raw material for the alkyl ethylbenzene is selected from one or more of methyl ethylbenzene, tert-butyl ethylbenzene, or other polyalkyl ethylbenzenes, preferably p-methyl ethylbenzene.

[0032] Furthermore, the reaction conditions are: a reaction temperature of 580–610 °C and a liquid hourly space velocity of 0.1–1.5 h⁻¹. 1 The reaction pressure is atmospheric pressure, and the molar ratio of water to alkyl ethylbenzene is 18–60.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] The catalyst for producing alkylstyrene provided by this invention has a better synergistic effect among its components, which is beneficial to improving the selectivity of the product alkylstyrene.

[0035] The catalyst for producing alkylstyrene provided by this invention comprises transition metals Y and Ti, which have a binary synergistic effect on improving the selectivity of alkylstyrene; and also comprises alkali metals, alkaline earth metals and transition metals, which have a ternary synergistic effect on improving the selectivity of alkylstyrene.

[0036] This invention first prepares a mixed solution of alkali metal source and alkaline earth metal source, then mixes it uniformly with a mixed solution of other components. During the preparation process, the catalyst is obtained by controlling process parameters such as the composition and ratio of each element, the wet mixing discharge temperature, and the calcination conditions. This catalyst is used in the production of alkylstyrene and is beneficial for improving the selectivity of the alkylstyrene product. Detailed Implementation

[0037] The technical solution of the present invention will be clearly and completely described below with reference to embodiments and comparative examples. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0038] The catalyst particles obtained by this invention can be in various shapes such as solid cylinder, hollow cylinder, trilobal, rhomboid, plum blossom, honeycomb, etc. There are no fixed limitations on their diameter and particle length. It is recommended that the catalyst be solid cylindrical particles with a diameter of 3 mm and a length of 5 to 10 mm.

[0039] The catalyst prepared in this invention was evaluated for activity in an isothermal fixed bed, and the process is briefly described below:

[0040] The reactants and steam are separately metered into a preheating mixer, where they are preheated and mixed into a gaseous state before entering the reactor. The reactor is heated by an electric heating wire to reach a predetermined temperature. The reactor is housed in a 1″ stainless steel tube, which can hold 100 mL of catalyst. The reactants exiting the reactor are condensed in water and their composition is analyzed by gas chromatography.

[0041] The conversion rate of alkyl ethylbenzene and the selectivity of alkyl styrene are calculated using the following formulas:

[0042]

[0043]

[0044] Alkyl styrene yield % = conversion % × selectivity %.

[0045] The present invention will be further illustrated below through examples.

[0046]

Example 1

[0047] The catalyst is prepared by: (1) dissolving and mixing potassium carbonate (equivalent to 17.20 parts K2O), sodium carbonate (equivalent to 0.45 parts Na2O), calcium hydroxide (equivalent to 2.11 parts CaO), and barium hydroxide (equivalent to 1.01 parts) in water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) mixing iron oxide red (equivalent to 53.06 parts Fe2O3), iron oxide yellow (equivalent to 13.26 parts Fe2O3), cerium oxalate (equivalent to 8.93 parts CeO2), and cerium nitrate (equivalent to 2.23 parts CeO2). Ammonium molybdate (equivalent to 1.58 parts MoO3), yttrium nitrate (equivalent to 0.15 parts Y2O3), TiO2 (0.02 parts), and sodium carboxymethyl cellulose (5.2 parts) were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 40 minutes. The material outlet temperature was 52.5℃. The mixture was then extruded into granules with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, it was calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 815℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0048] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0049]

Example 2

[0050] The catalyst is prepared by (1) dissolving and mixing potassium carbonate equivalent to 17.20 parts K2O, sodium carbonate equivalent to 0.45 parts Na2O, calcium hydroxide equivalent to 2.11 parts CaO, and barium hydroxide equivalent to 1.01 parts with water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) dissolving and mixing iron oxide red equivalent to 53.06 parts Fe2O3, iron oxide yellow equivalent to 13.26 parts Fe2O3, cerium oxalate equivalent to 8.93 parts CeO2, cerium nitrate equivalent to 2.23 parts CeO2, and barium hydroxide equivalent to 1.01 parts. 58 parts of ammonium molybdate (MoO3), yttrium nitrate (equivalent to 0.15 parts of Y2O3), 0.02 parts of ZrO2, 2.6 parts of sodium carboxymethyl cellulose, and 2.6 parts of hydroxyethyl cellulose were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 35 minutes. The discharge temperature of the material was 45.2℃. The mixture was then extruded into granules with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 65℃ for 5 hours, then at 80℃ for 12 hours. Finally, it was calcined at 385℃ for 3 hours, 670℃ for 4 hours, and 820℃ for 4 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0051] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0052]

Example 3

[0053] The catalyst preparation method is as follows: (1) Dissolve and mix potassium carbonate equivalent to 17.20 parts K2O, sodium carbonate equivalent to 0.45 parts Na2O, calcium hydroxide equivalent to 2.11 parts CaO, and barium hydroxide equivalent to 1.01 parts with water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) Dissolve and mix iron oxide red equivalent to 53.06 parts Fe2O3, iron oxide yellow equivalent to 13.26 parts Fe2O3, cerium oxalate equivalent to 8.93 parts CeO2, cerium nitrate equivalent to 2.23 parts CeO2, and barium hydroxide equivalent to 17.5% of the total weight of the catalyst raw materials to obtain mixture I; 1.58 parts of ammonium molybdate (MoO3), 0.15 parts of ZrO2, 0.02 parts of TiO2, 2.6 parts of hydroxypropyl methylcellulose, and 2.4 parts of sodium carboxymethyl cellulose were stirred in a kneader for 1.0 hour. Then, mixture I was added and wet-mixed, and kneaded for 35 minutes. The temperature of the material at the outlet was 41.5℃. After that, it was extruded into particles with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 55℃ for 5 hours, then at 95℃ for 12 hours, and then calcined at 375℃ for 4 hours, 700℃ for 4 hours, and 870℃ for 3 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0054] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0055]

Example 4

[0056] The catalyst preparation method is as follows: (1) Dissolve and mix potassium carbonate (equivalent to 17.20 parts K2O), sodium carbonate (equivalent to 0.45 parts Na2O), calcium hydroxide (equivalent to 2.11 parts CaO), and barium hydroxide (equivalent to 1.01 parts) in water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) Mix iron oxide red (equivalent to 53.06 parts Fe2O3), iron oxide yellow (equivalent to 13.26 parts Fe2O3), cerium oxalate (equivalent to 8.93 parts CeO2), and cerium hydroxide (equivalent to 2.23 parts CeO2) in water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; Cerium nitrate, ammonium molybdate equivalent to 1.58 parts MoO3, 0.15 parts Sc2O3, 0.02 parts ZrO2, and 4.6 parts hydroxyethyl cellulose were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 45 minutes. The temperature of the material discharged was 42.7℃. The mixture was then extruded into particles with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 85℃ for 12 hours, and finally calcined at 285℃ for 4 hours, 680℃ for 5 hours, and 805℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0057] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0058]

Example 5

[0059] The catalyst is prepared by (1) dissolving and mixing potassium carbonate (equivalent to 17.29 parts K2O), sodium carbonate (equivalent to 1.25 parts Na2O), calcium hydroxide (equivalent to 1.28 parts CaO), and barium hydroxide (equivalent to 0.95 parts) with water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) mixing iron oxide red (equivalent to 53.06 parts Fe2O3), iron oxide yellow (equivalent to 13.26 parts Fe2O3), cerium oxalate (equivalent to 8.93 parts CeO2), and cerium nitrate (equivalent to 2.23 parts CeO2). Ammonium molybdate (equivalent to 1.58 parts MoO3), yttrium nitrate (equivalent to 0.16 parts Y2O3), TiO2 (0.01 parts), and sodium carboxymethyl cellulose (5.8 parts) were stirred in a kneader for 1.4 hours. Then, mixture I was added for wet mixing and kneading for 30 minutes. The material outlet temperature was 48.5℃. The mixture was then extruded into granules with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, it was calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 815℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0060] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0061]

Example 6

[0062] The catalyst is prepared by: (1) dissolving and mixing potassium carbonate (equivalent to 16.21 parts K2O), sodium carbonate (equivalent to 1.75 parts Na2O), calcium hydroxide (equivalent to 2.31 parts CaO), and barium hydroxide (equivalent to 0.50 parts) in water at a weight of 17.5% of the total catalyst raw materials to obtain mixture I; (2) mixing iron oxide red (equivalent to 53.06 parts Fe2O3), iron oxide yellow (equivalent to 13.26 parts Fe2O3), cerium oxalate (equivalent to 8.93 parts CeO2), and cerium nitrate (equivalent to 2.23 parts CeO2). Ammonium molybdate (equivalent to 1.58 parts MoO3), yttrium nitrate (equivalent to 0.15 parts Y2O3), ZrO2 (0.02 parts), and sodium carboxymethyl cellulose (5.5 parts) were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 35 minutes. The material outlet temperature was 41.5℃. The mixture was then extruded into granules with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, it was calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 825℃ for 4 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0063] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0064]

Example 7

[0065] The catalyst is prepared by (1) dissolving and mixing potassium carbonate (equivalent to 15.51 parts K2O), sodium carbonate (equivalent to 1.39 parts Na2O), calcium hydroxide (equivalent to 3.52 parts CaO), and barium hydroxide (equivalent to 0.35 parts) in water at a weight of 17.5% of the total catalyst raw materials to obtain mixture I; (2) mixing iron oxide red (equivalent to 53.06 parts Fe2O3), iron oxide yellow (equivalent to 13.26 parts Fe2O3), cerium oxalate (equivalent to 8.93 parts CeO2), and nitrate (equivalent to 2.23 parts CeO2) in water at a weight of 17.5% of the total catalyst raw materials to obtain mixture I; Cerium molybdate, ammonium molybdate equivalent to 1.58 parts MoO3, 0.15 parts Sc2O3, 0.02 parts ZrO2, and 4.1 parts sodium carboxymethyl cellulose were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 40 minutes. The temperature of the material discharged was 50.2℃. The mixture was then extruded into particles with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 90℃ for 12 hours, and then calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 815℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0066] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0067]

Example 8

[0068] The catalyst preparation method is as follows: (1) Dissolve and mix potassium carbonate equivalent to 17.23 parts K2O, sodium carbonate equivalent to 0.45 parts Na2O, calcium hydroxide equivalent to 2.11 parts CaO, and barium hydroxide equivalent to 1.01 parts with water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) Dissolve and mix iron oxide red equivalent to 53.14 parts Fe2O3, iron oxide yellow equivalent to 13.29 parts Fe2O3, cerium oxalate equivalent to 8.94 parts CeO2, and barium hydroxide equivalent to 2.01 parts of CaO. 24 parts of cerium nitrate (CeO2), ammonium molybdate equivalent to 1.58 parts of MoO3, and 5.0 parts of sodium carboxymethyl cellulose were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 38 minutes. The discharge temperature of the material was 62.5℃. The mixture was then extruded into particles with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, it was calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 800℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0069] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0070]

Comparative Example 1

[0071] The catalyst preparation method is as follows: (1) Dissolve and mix potassium carbonate equivalent to 13.95 parts K2O, sodium carbonate equivalent to 0.10 parts Na2O, calcium hydroxide equivalent to 0.11 parts CaO, and barium hydroxide equivalent to 1.01 parts with water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) Dissolve and mix iron oxide red equivalent to 55.82 parts Fe2O3, iron oxide yellow equivalent to 13.95 parts Fe2O3, cerium oxalate equivalent to 10.78 parts CeO2, and barium hydroxide equivalent to 1.01 parts of CaO. 2.70 parts of cerium nitrate (CeO2), ammonium molybdate equivalent to 1.58 parts of MoO3, and 5.0 parts of sodium carboxymethyl cellulose were stirred in a kneader for 1.2 hours. Then, mixture I was added and wet-mixed, and kneaded for 38 minutes. The temperature of the material discharged was 62.5℃. The mixture was then extruded into particles with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, it was calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 800℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0072] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0073] [Comparative Example 2]

[0074] The catalyst preparation method is as follows: (1) Dissolve and mix potassium carbonate equivalent to 17.20 parts K2O, sodium carbonate equivalent to 0.45 parts Na2O, calcium hydroxide equivalent to 2.11 parts CaO, and barium hydroxide equivalent to 1.01 parts in water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) Mix iron oxide red equivalent to 53.06 parts Fe2O3, iron oxide yellow equivalent to 13.26 parts Fe2O3, cerium oxalate equivalent to 8.93 parts CeO2, cerium nitrate equivalent to 2.23 parts CeO2, and the phase The following mixtures were prepared: 1.58 parts of ammonium molybdate (MoO3), 0.165 parts of yttrium nitrate (Y2O3), 0.005 parts of TiO2, and 5.2 parts of sodium carboxymethyl cellulose were mixed in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 40 minutes. The discharge temperature of the material was 52.5℃. The mixture was then extruded into particles with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, the particles were calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 815℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0075] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0076] [Comparative Example 3]

[0077] The catalyst is prepared by: (1) dissolving and mixing potassium carbonate (equivalent to 16.15 parts K2O), sodium carbonate (equivalent to 0.14 parts Na2O), calcium hydroxide (equivalent to 0.48 parts CaO), and barium hydroxide (equivalent to 4.00 parts) with water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) mixing iron oxide red (equivalent to 53.06 parts Fe2O3), iron oxide yellow (equivalent to 13.26 parts Fe2O3), cerium oxalate (equivalent to 8.93 parts CeO2), and cerium nitrate (equivalent to 2.23 parts CeO2). Ammonium molybdate (equivalent to 1.58 parts MoO3), yttrium nitrate (equivalent to 0.15 parts Y2O3), TiO2 (0.02 parts), and sodium carboxymethyl cellulose (5.2 parts) were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 40 minutes. The material outlet temperature was 52.5℃. The mixture was then extruded into granules with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, it was calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 815℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0078] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0079] [Comparative Example 4]

[0080] The catalyst is prepared by (1) dissolving and mixing potassium carbonate (equivalent to 14.01 parts K2O), sodium carbonate (equivalent to 0.11 parts Na2O), calcium hydroxide (equivalent to 2.11 parts CaO), and barium hydroxide (equivalent to 1.01 parts) with water accounting for 17.5% of the total weight of the catalyst raw materials to obtain mixture I; (2) mixing iron oxide red (equivalent to 55.88 parts Fe2O3), iron oxide yellow (equivalent to 13.97 parts Fe2O3), cerium oxalate (equivalent to 8.93 parts CeO2), and cerium nitrate (equivalent to 2.23 parts CeO2). Ammonium molybdate (equivalent to 1.58 parts MoO3), yttrium nitrate (equivalent to 0.15 parts Y2O3), TiO2 (0.02 parts), and sodium carboxymethyl cellulose (5.2 parts) were stirred in a kneader for 1.2 hours. Then, mixture I was added for wet mixing and kneading for 40 minutes. The material outlet temperature was 52.5℃. The mixture was then extruded into granules with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours. Finally, it was calcined at 365℃ for 4 hours, 650℃ for 5 hours, and 815℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0081] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0082] [Comparative Example 5]

[0083] The catalyst is prepared by mixing potassium carbonate (equivalent to 17.20 parts K₂O), sodium carbonate (equivalent to 0.45 parts Na₂O), calcium hydroxide (equivalent to 2.11 parts CaO), barium hydroxide (equivalent to 1.01 parts), iron oxide red (equivalent to 53.06 parts Fe₂O₃), iron oxide yellow (equivalent to 13.26 parts Fe₂O₃), cerium oxalate (equivalent to 8.93 parts CeO₂), cerium nitrate (equivalent to 2.23 parts CeO₂), and [the following is a separate, unrelated sentence:] [The catalyst is prepared by mixing potassium carbonate (equivalent to 17.20 parts K₂O), sodium carbonate (equivalent to 0.45 parts Na₂O), calcium hydroxide (equivalent to 2.11 parts CaO), barium hydroxide (equivalent to 1.01 parts), iron oxide red (equivalent to 53.06 parts Fe₂O₃), iron oxide yellow (equivalent to 13.26 parts Fe₂O₃), cerium oxalate (equivalent to 8.93 parts CeO₂), cerium nitrate (equivalent to 2.23 parts CeO₂), and [the following is a separate, unrelated sentence:] [The catalyst is prepared by mixing potassium carbonate (equivalent to 17.20 parts K₂O), sodium carbonate (equivalent to 0.45 parts Na₂O), calcium hydroxide (equivalent to 2.11 parts CaO), barium hydroxide (equivalent to 1.01 parts), iron oxide red (equivalent to 53.06 parts Fe₂O₃), iron oxide yellow (equivalent to 13.26 parts Fe₂O₃), cerium oxalate (equivalent to 8.93 parts CeO₂), cerium nitrate (equivalent to 2.23 Ammonium molybdate, yttrium nitrate equivalent to 0.15 parts Y₂O₃, 0.02 parts TiO₂, and 5.2 parts sodium carboxymethyl cellulose were stirred in a kneader for 1.2 hours. Then, water (17.5% of the total weight of the catalyst raw materials) was added for wet mixing and kneading for 60 minutes. The temperature of the material discharged was 78.5℃. The mixture was then extruded into particles with a diameter of 3 mm and a length of 5 mm, placed in an oven, and dried at 50℃ for 5 hours, then at 100℃ for 12 hours, and finally calcined at 815℃ for 5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0084] p-Methylethylbenzene and steam were introduced into an isothermal bed reactor, where the materials contacted the aforementioned iron-based catalyst. The reaction temperature was 590°C, the reaction pressure was atmospheric pressure, and the liquid hourly space velocity (LHSV) was 0.8 h⁻¹. -1 The evaluation was conducted under the condition of a water vapor / p-methylethylbenzene molar ratio of 40, and the test results are listed in Table 2.

[0085] Table 1 Catalyst Composition for Each Example

[0086]

[0087] Table 2. Evaluation results of each catalyst example.

[0088]

[0089] The embodiments described above are merely detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments, that is, the present invention does not depend on the steps described in the above embodiments to be implemented. In summary, any improvements made to the present invention by those skilled in the art, including the substitution of the raw materials and additives described in the present invention, the selection of specific implementation methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. The application of a catalyst for the production of alkylstyrene in the dehydrogenation reaction of alkylethylbenzene to alkylstyrene, characterized in that, The raw material for alkyl ethylbenzene is selected from one or more of methyl ethylbenzene, tert-butyl ethylbenzene, or other polyalkyl ethylbenzenes; the catalyst used for the production of alkyl styrene comprises the following components by weight percentage of the total catalyst: (a) 65%~70% Fe2O3; (b) 16%–20% alkali metal oxides; (c) 9.0%~13.5% CeO2; (d) 0.5%~3.5% MoO3; (e) 1.1% to 4.5% alkaline earth metal oxides; The weight ratio of alkali metals to alkaline earth metals, calculated as oxides, is 4 to 10. The alkali metals are K and Na, and the alkaline earth metals are Ba and Ca; the Na2O content in the alkali metals accounts for 1.5% to 10.0% of the total weight of the alkali metal oxides, and the CaO content in the alkaline earth metals accounts for 50% to 95% of the total weight of the alkaline earth metal oxides; The catalyst contains transition metals Y and Ti, with a weight content of 0.01% to 0.50% based on oxides, wherein the weight ratio of Y to Ti based on oxides is 5 to 25.

2. The application according to claim 1, characterized in that, The raw material for alkyl ethylbenzene is p-methylethylbenzene.

3. The application according to claim 1, characterized in that, The reaction conditions for the dehydrogenation of alkylethylbenzene to produce alkylstyrene are: reaction temperature of 580~610℃ and liquid hourly space velocity of 0.1~1.5 h⁻¹. -1 The reaction pressure is atmospheric pressure, and the molar ratio of water to alkyl ethylbenzene is 18~60.

4. The application according to claim 1, characterized in that, In the catalyst, the weight content of transition metals Y and Ti, calculated as oxides, is 0.1% to 0.3%.

5. The application according to claim 1, characterized in that, The method for preparing the catalyst for producing alkylstyrene includes the following steps: (1) Dissolve and mix the required amounts of alkali metal source and alkaline earth metal source in water to obtain mixture I; (2) The transition metal precursor is mixed with the required amount of iron source, cerium source, molybdenum source and pore-forming agent, and then mixed with mixture I, wet-mixed, shaped, dried and calcined to obtain the catalyst.

6. The application according to claim 5, characterized in that, The pore-forming agent is selected from one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, guar gum, methyl cellulose, and hydroxyethyl cellulose, and its addition amount is 3% to 5% of the total weight of the catalyst raw materials.

7. The application according to claim 5, characterized in that, In step (2), the material discharge temperature is controlled at 40~75℃ during the wet mixing process.

8. The application according to claim 5, characterized in that, In step (2), the roasting is divided into three stages: the first stage is roasted at 250~380℃ for 4~8h, the second stage is roasted at 600~720℃ for 4~8h, and the third stage is roasted at 780~870℃ for 3~6h.

Citation Information

Patent Citations

  • Process for the preparation of META-and para-tertiarybutylstyrenes

    US3631213A

  • Diethylbenzene dehydrogenation catalyst and preparation method thereof

    CN107790149A

  • Catalysts for ethyl benzene dehydrogenation preparation of styrene

    CN1883796A